On the mechanism of the antiarrhythmic action of fabomotizole hydrochloride in alcoholic cardiomyopathy - I. A. Miroshkina; L. M. Kozhevnikova; I. B. Tsorin; V. N. Stolyaruk; M. B. Vititnova; S. A. Kryzhanovskii; A. D. Durnev (LLC "Publisher OKI", 2021)
It is known that the alcoholic cardiomyopathy (ACMP) is the main reason for lethality from chronic alcoholism. For ACMP the risk of development of malignant violations of a heart rhythm which result approximately at 40% of such patients is sudden heart death is extremely high. Materials and methods. Experiments were made on the ACMP translational model developed by us which is formed at rats by the end of the 24th week of compulsory reception of 10 % of ethanol solution. For studying the mechanisms which are the responsible of antiarrhythmic action of a fabomotizole dihydrochloride used a complex of morphohistological, electrophysiological and molecular researches. Results. It is shown that against the background of systematic therapy fabomotizole dihydrochloride (15 mg/kg, i.p.) daily within 28 days after 24 weeks of alcoholization, in comparison with alcoholized control the fat dystrophy of a myocardium significantly decreases and the threshold of electric fibrillation of heart ventricles is restored. According to results of molecular researches, a fabomotizole dihydrochloride significantly suppresses revealed in control alkoholized animals the abnormal mRNA expression of key receptor genes and proteins responsible for maintenance in cardiomyocytes of a homeostasis of ions of Ca++ and regulation of their rhythmic activity: regulatory proteins Epac1 (p = 0.021), Epac2 (p = 0.018), CaM (p = 0.00001) and also RyR2 (p = 0.031), IP3R2 (p = 0.006) receptors. Conclusion. The obtained results suggest that antiarrhythmic action of a fabomotizole dihydrochloride in the conditions of ACMP is connected with its ability to suppress abnormal activity of regulatory proteins Epac2 and RyR2, IP3R2 receptors.